2022
DOI: 10.2215/cjn.16801221
|View full text |Cite
|
Sign up to set email alerts
|

Association of Histologic Parameters with Outcome in C3 Glomerulopathy and Idiopathic Immunoglobulin-Associated Membranoproliferative Glomerulonephritis

Abstract: Background and objectivesC3 glomerulopathy and idiopathic Ig-associated membranoproliferative GN are kidney diseases characterized by abnormal glomerular complement C3 deposition. These conditions are heterogeneous in outcome, but approximately 50% of patients develop kidney failure within 10 years.Design, setting, participants, & measurementsTo improve identification of patients with poor prognosis, we performed a detailed analysis of percutaneous kidney biopsies in a large cohort of patients. Using a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
(83 reference statements)
3
25
0
Order By: Relevance
“…Recently, it has been shown that in three of 11 individuals initially diagnosed with IC‐MPGN, the diagnosis changed to C3GN following a second biopsy. 108 These findings are consistent with the hypothesis that during the course of C3G, there may be episodes of IC deposition, possibly triggered by infections.…”
Section: Two Prototypical Complement‐mediated Kidney Diseasessupporting
confidence: 90%
See 2 more Smart Citations
“…Recently, it has been shown that in three of 11 individuals initially diagnosed with IC‐MPGN, the diagnosis changed to C3GN following a second biopsy. 108 These findings are consistent with the hypothesis that during the course of C3G, there may be episodes of IC deposition, possibly triggered by infections.…”
Section: Two Prototypical Complement‐mediated Kidney Diseasessupporting
confidence: 90%
“…This likely relates to IC induced by infections or other triggers that initiate the disease in patients who have an underlying AP abnormality, and C3‐dominance may become evident following classical pathway inactivation after the resolution of infection or after immunosuppressive therapy. Recently, it has been shown that in three of 11 individuals initially diagnosed with IC‐MPGN, the diagnosis changed to C3GN following a second biopsy 108 . These findings are consistent with the hypothesis that during the course of C3G, there may be episodes of IC deposition, possibly triggered by infections.…”
Section: Two Prototypical Complement‐mediated Kidney Diseasessupporting
confidence: 74%
See 1 more Smart Citation
“…Our group has recently proposed a simple and easy to use nomogram to predict the risk of kidney failure in C3 glomerulopathy (8) on the basis of the eGFR, proteinuria, and total chronicity score at baseline, although these results have not yet been validated in independent cohorts. The study by Lomax-Browne et al (6) is undoubtedly one of the most important cohorts published to date and sheds light on the main histologic determinants of outcomes in C3 glomerulopathy/Ig-mediated MPGN. Their main strengths are the large number of patients included from different countries, the inclusion of well-characterized idiopathic Ig-MPGN, and most importantly, the centralized review of all kidney biopsies.…”
mentioning
confidence: 99%
“…have not yet been validated in independent cohorts. The study by Lomax-Browne et al (6) is undoubtedly one of the most important cohorts published to date and sheds light on the main histologic determinants of outcomes in C3 glomerulopathy/Ig-mediated MPGN. Their main strengths are the large number of patients included from different countries, the inclusion of well-characterized idiopathic Ig-MPGN, and most importantly, the centralized review of all kidney biopsies.…”
mentioning
confidence: 99%